THE USE OF ARTIFICIAL INTELLIGENCE IN EDUCATION: OPPORTUNITIES AND RISKS - Kholturayeva Rukhshona; Khidirova Muharram; Nurullayeva Hulkar (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: This article explores the role, opportunities, and potential risks of artificial intelligence (AI) technologies in the field of education. It highlights how AI can personalize learning, automate assessment systems, and improve education quality. At the same time, it discusses possible negative outcomes, such as over-reliance on technology, data privacy issues, and the reduction of human interaction. The article concludes by emphasizing the need for responsible and cautious use of AI in education.